2012
DOI: 10.17221/210/2011-pse
|View full text |Cite
|
Sign up to set email alerts
|

Role of abscisic acid and drought stress on the activities of antioxidant enzymes in wheat

Abstract: The effect of drought stress and abscisic acid (ABA) applied at tillering stage (55 days after sowing) was compared in 2 wheat cultivars differing in drought tolerance. The activities of superoxide dismutase (SOD) and peroxidase (POD) and contents of endogenous ABA in plants were measured at 3 days of drought stress in cv. Chakwal-97 (drought tolerant) and cv. Punjab-96 (drought susceptible). ABA was applied at 10 -6 mol/L as presowing seed treatment for 18 h. Drought tolerant cultivar has a more efficient mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(37 citation statements)
references
References 22 publications
4
30
0
3
Order By: Relevance
“…It was reported that, the spike length, number of grains per spike and weight of 1000 grain weight were significantly decreased in drought stressed wheat plants (Bano et al, 2012). It was reported that the deficiency of water causes decline in yield traits of crop plants probably by disrupting leaf gas exchange which limits the assimilate translocation and dry matter partitioning (Farooq et al, 2009).…”
Section: The Effects Of Drought and Ca + Treatments Are Prolonged To mentioning
confidence: 99%
“…It was reported that, the spike length, number of grains per spike and weight of 1000 grain weight were significantly decreased in drought stressed wheat plants (Bano et al, 2012). It was reported that the deficiency of water causes decline in yield traits of crop plants probably by disrupting leaf gas exchange which limits the assimilate translocation and dry matter partitioning (Farooq et al, 2009).…”
Section: The Effects Of Drought and Ca + Treatments Are Prolonged To mentioning
confidence: 99%
“…550, 2967,621 may be indication of the cellular evaluated ROS, since the amount of POD enzyme present in aerobic cells is directly related to the oxidative state of the cell (Apel & Hurt, 2004). In the earlier studies, the increase in the activities of antioxidant enzymes by ABA application was reported in different cultivars of wheat (Bano et al, 2012). So as an adaptive enzyme in antioxidant system, Class-III BsPOD play an important role in protecting membrane lipids from peroxidation and in reducing the cell damage being caused by ABA-induced oxidative stress in embryos.…”
Section: Aba-induced Changes In Boiling Stable Pod Activity and Isoenmentioning
confidence: 95%
“…It w as report ed that, the spike length and numb er of grains p er spike were significantl y decreas ed under drought stress of wheat plant (Bano et al, 2012). Also, it w as found t hat w hen maiz e plants were exp osed t o drought stress at s eedling stage, it l ed t o s ubstanti al reduc tion in yield components s uch a ker nel row s/c ob, kernel number/r ow, 100 k ernels w eight , k ernels/c ob, grain yi eld/plant ( Anj um et al, 2011).…”
Section: +mentioning
confidence: 97%